Development of cathodes for methanol and ethanol fuelled lowtemperature (300.600 .C)solid oxide fuel cells - Mat, M.D.; Liu, X.; Zhu, Z.; Zhu, B.
We have made extensive efforts to develop various compatible cathode materials for the ceria-carbonate composite (CCC)electrolytes to be used in direct alcohol fuelled solid oxide fuel cells (DLFC). The following cathode materials were mainly investigated: (i)BSCF (BaSrCoFeO)perovskite oxide; (ii)LFN (LaFeO-based oxides, e.g. LaFe0.8Ni0.2O3)perovskite oxides; (iii)bi- or tri-phase metal oxides with or without lithiation. A number of copper- and nickel-based anode composites were also developed for methanol and ethanol with maximum catalytic activity. The tri-metal oxide (CuNiOx.ZnO)cathode produced the maximum power density output of 500mW/cm.2 at 580 .C for DLFC with methanol operation.
Keywords: SOLID OXIDE FUEL CELL; DIRECT ALCOHOL FUELLING; CATHODE MATERIALS; METHANOL ETHANOL; CERIA COMPOSITE ELECTROLYTE